A case of acrodysostosis: a rare primary bone dysplasia - Vasava, Roopal; Tank, Bhargav; Jain, Abhilasha (International Journal of Research in Medical Sciences, 2018)
Acrodysostosis is a rare skeletal dysplasia characterized by brachydactyly, facial dysostosis and nasal hypoplasia. Diagnostic approach to this disorder is based on clinical, radiological and hormonal assays. We present a case of 11-year-old female child who presented with the complaint of short stubby hands and feet since birth and facial dysmorphism. Her skeletal survey revealed typical radiographic features of acrodysostosis. Hormonal assays did not reveal any significant abnormality. In this case report, we would like to highlight the clinical and radiological features of this disorder which could be helpful in diagnosis of this rare disease.